A juice extractor can simplify the downstream processing of plant-derived biopharmaceutical proteins compared to blade-based homogenizers. Issue 5 (May 2015) - Buyel, J.F.; Fischer, R.
Highlights Juice extraction from tobacco leaves increases protein concentrations by ∼3-fold. Juice extraction reduces process volumes by 80% compared to blender extraction. Total process costs can be reduced by 10–30% using juice extraction. Juice extraction allows continuous processing and is easy to scale up. Juice extraction is compatible with flocculation and the heat precipitation of host cell proteins.